Molybdenite Re-Os and zircon U-Pb geochronology, Lu-Hf isotope and geochemistry constraints on the genesis of the Jinxi Cu deposit, southern Fujian, South China - Ren, Chenghao; Sun, Yandong; Zhou, Qunmao; She, Hongquan; Chen, Maohong; Wang, Dongsheng; Li, Baoliang (Ore geology reviews, 2025)
[Display omitted] •Granodiorite from the Jinxi Cu mine was characterized.•Granodiorite from the Jinxi Cu deposit belongs to the high-K calc-alkaline series.•Granodiorite diagenesis and mineralization occurred in the late Early Cretaceous.•Granodiorite in the Jinxi Cu deposit is supposedly a type I granite. The Jinxi Cu deposit, situated on the southeastern margin of the Cathaysian Plate within the Shanghang-Yunxiao tectonic-magmatic metallogenic belt, is a medium-sized deposit discovered in the region in recent years. This study employs molybdenite Re-Os and zircon U-Pb dating, along with Lu-Hf isotopic and whole-rock geochemical analyses, to elucidate the rock-forming and ore-forming processes, as well as the genesis of the Jinxi deposit. The results show that the granodiorites related to mineralization in the mining area belong to the high-potassium calc-alkaline series, characterized by high K2O levels, low SiO2, and low TiO2 concentrations. Analysis of rare earth elements (REE) and trace elements reveals that the granodiorites are enriched in light rare earth elements (LREE) and exhibit weak negative Eu anomalies. Integrating these findings with evidence from related research, the granodiorites of the Jinxi Cu deposit can be reasonably classified as I-type granites. Zircon Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA − ICP − MS) dating of the granodiorites yields an age of 104.2 ± 0.4 Ma. The zircon εHf(t) values for the granodiorites range from −2.49 to 1.58, with two-stage model ages (TDM2) ranging from 1.08 to 1.32 Ga. Re − Os isotopic dating of molybdenite samples yields an isochron age of 104.6 ± 3.7 Ma for the ore bodies, indicating that the formation of the Jinxi Cu deposit during the late Yanshanian period is primarily associated with the emplacement of intrusive rocks. Integrating field observations, wall-rock alteration characteristics, geochronological data, and isotopic analyses, the Jinxi deposit is identified as a high- to medium-temperature magmatic-hydrothermal vein-type copper deposit. The formation of the Jinxi granodiorite and its associated mineralization is attributed to the subduction of the Paleo-Pacific Plate along the southeastern coastal region during the late Early Cretaceous period (110–90 Ma).